Synthesis of Mesoporous Carbon from Merbau Wood (Intsia spp.) by Microwave Method as Ni Catalyst Support for α-Cellulose Hydrocracking - Andaru Dena Prasiwi; Wega Trisunaryanti; Triyono Triyono; Iip Izul Falah; Darma Santi; Muhammad Fajar Marsuki (Indonesian Journal of Chemistry, 2019)
Synthesis of mesoporous carbon from Merbau wood (Intsia spp.) waste by microwave method as nickel catalyst support for α-cellulose hydrocracking had been carried out. The Merbau wood sawdust was carbonized at 800 °C to produce C800 and the C800 was treated by microwave irradiation (399 W) for 5 min to produce C800MW. The Merbau wood flakes, which were only treated by microwave irradiation (399 Watts) for 30 min produced CMW. Wet impregnation technique was carried out to disperse the Ni metal (1.0, 1.5, and 2.0 wt.%) onto the best mesoporous carbon. The mesoporous carbons were analyzed by Fourier Transform Infra-Red Spectroscopy (FTIR), Surface Area Analyzer (SAA) and Scanning Electron Microscopy (SEM). The hydrocracking of pyrolyzed α-cellulose was carried out at 400 °C. The liquid product was analyzed by Gas Chromatograph-Mass Spectrometer (GC-MS). The results showed that the C800MW was the best performance carbon and it had a specific surface area, total pore volume, average pore diameter and acidity of 364.12 m2/g, 0.28 cm3/g, 3.03 nm, and 2.18 mmol/g, respectively. The Ni1.5/C800MW catalyst produced the highest conversion of liquid product (58.76 wt.%) than the Ni1/C800MW (57.51 wt.%) and Ni2/C800MW (34.18 wt.%).